2011
DOI: 10.1021/jp203080j
|View full text |Cite
|
Sign up to set email alerts
|

Bond Characterization on a Cr–Cr Quintuple Bond: A Combined Experimental and Theoretical Study

Abstract: A combined experimental and theoretical charge density study on a quintuply bonded dichromium complex, Cr(2)(dipp)(2) (dipp = (Ar)NC(H)N(Ar) and Ar = 2,6-i-Pr(2)-C(6)H(3)), is performed. Two dipp ligands are bridged between two Cr ions; each Cr atom is coordinated to two N atoms of the ligands in a linear fashion. The Cr atom is in a low oxidation state, Cr(I), and in low coordination number condition, which stabilizes a metal-metal multiple bond, in this case, a quintuple bond. Indeed, it gives an ultrashort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 78 publications
4
52
0
1
Order By: Relevance
“…In 2005, Power et al [86] reported the synthesis of the first isolable formal quintuply bonded (σ 2 π 4 δ 4 ) dichromium complex ArCrCrAr (Ar = 2,6-(2,6-iPr 2 C 6 H 3 ) 2 C 6 H 3 ) with an unusually short Cr-Cr distance (1.835 Å). This report stimulated several theoretical and experimental studies [87][88][89][90][91][92][93][94][95] in which the nature of the Cr-Cr bond was probed. Since then, several complexes featuring ultra-short Cr-Cr bonds of around 1.75 Å have been identified [88][89][90][94][95][96].…”
Section: High Bond Orders In Transition Metalssupporting
confidence: 56%
“…In 2005, Power et al [86] reported the synthesis of the first isolable formal quintuply bonded (σ 2 π 4 δ 4 ) dichromium complex ArCrCrAr (Ar = 2,6-(2,6-iPr 2 C 6 H 3 ) 2 C 6 H 3 ) with an unusually short Cr-Cr distance (1.835 Å). This report stimulated several theoretical and experimental studies [87][88][89][90][91][92][93][94][95] in which the nature of the Cr-Cr bond was probed. Since then, several complexes featuring ultra-short Cr-Cr bonds of around 1.75 Å have been identified [88][89][90][94][95][96].…”
Section: High Bond Orders In Transition Metalssupporting
confidence: 56%
“…[2][3][4] For instance, the length of the CrÀCr quadruple bond for Cr 2 4 + complexesv aries from 1.830 to 2.541 . [5] In addition, for most of the metal-metal bonds, the effectiveb ond order (EBO) is dramatically lower than the FBO. Aw ell-known example is the EBO of 3.2valenceu nits (v.u.)…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the CrÀCr quintuple bond of the type II complex was recently corroborated by charge-density studies. [9] Preliminary reactivity studies on the type II complexes indicate these univalent and low-coordinate dinuclear species are reactive towards unsaturated organic functionalities and small molecules. [10,11] Compared to the many type II complexes, only one example of the type III complex, [Cr 2 {m-HC(N-2,6-Me 2 C 6 H 3 ) 2 } 3 ] À (1), was recently reported, although such type of species was proposed by Hoffmann et al in 1979.…”
mentioning
confidence: 99%